An unexpectedly diverse new genus of catfishes (Siluriformes, Heptapteridae) endemic to the Magdalena River basin, Colombia - Donascimiento Montoya, Carlos Luis (2025)
A new genus of heptapterid catfish, Magdalenichthys gen. nov., largely ignored for the past two decades is herein described. Comprehensive examination of specimens in Colombian ichthyological collections and additional samplings in the Magdalena basin were the base for an integral analysis using morphological characters, DNA barcode delimitation, and molecular phylogenetic analyses to assess monophyly and relationships of the new genus, and to delimit and diagnose four new species, Magdalenichthys lundbergi sp. nov., Magdalenichthys mompox sp. nov., Magdalenichthys poira sp. nov., and Magdalenichthys yariguies sp. nov., endemic to the Magdalena basin. The new genus is phylogenetically diagnosed. Maximum likelihood, Bayesian inference, and coalescent-based analyses with ultraconserved elements (UCEs) data, place the new genus as sister to Phenacorhamdia, within a clade also containing Cetopsorhamdia and Pariolius, consistent with the finding of two apomorphic characters shared by the new genus and Phenacorhamdia. The biogeographic pattern of the new genus (restricted to the Magdalena basin) is also discussed.